Urticaria and Angioedema – More than just Skin Deep! - Jeanette Holtzhausen (South African Family Practice)
Urticaria and angioedema are characterized by pruritic hives and sometimes swelling of deeper mucocutaneous layers. Urticaria is caused by release of histamine and other mediators from mast cells. A cut-off of six weeks distinguishes acute and chronic forms, as these seem to differ regarding etiological and response patterns. Angioedema may be histaminergic or due to factors involving the bradykinin pathway. Medications such as ACE-Inhibitors or conditions affecting the C1-esterase inhibitor enzyme are potential causes.